Aloha, Kanani - Yee, Lisa.; Davis, Sarah, 1971- (Middleton, WI : American Girl, 2011)
"Meet Kanani Akina. When Kanani's cousin Rachel comes to stay for a month, Kanani can't wait to show her what life is like in a friendly Hawaiian town--from eating shave ice to snorkeling with sea turtles. But Rachel seems homesick and unhappy. Kanani tries hard to help Rachel feel at home and have fun, but nothing seems to work-- until an urgent animal rescue on the beach brings the girls together."--P. [4] of cover.
"American girl."
Ages 8 and up.
Keywords: Cousins -- Juvenile fiction; Friendship -- Juvenile fiction; Monk seals -- Juvenile fiction; Hawaii -- Juvenile fiction